HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN MOTIVASI MELANJUTKAN SEKOLAH MENENGAH KEJURUAN (SMK) - Humaera, Zuyun Nela (EMPATHY Jurnal Fakultas Psikologi, 2013)
Â AbstractHis study aims to examine the relationship between family support and motivation to continue vocational high school (SMK). Research method is the independent variable while the family support for the dependent variable was entered vocational motivation. The population in this study class VIII students of SMP N1 Tunjungan Blora totaled 80 subjects. Methods of data collection using a scale of Family Support and Motivation scales Sign SMK. The validity of the use that content validity for its reliability expressed by the coefficient of reliability that the numbers are in the range from 0 to 1.00 then the reliability of each scale was analyzed by using the formula of Cronbach alpha. For the data analysis, this study uses product moment analysis, data analysis was performed using the computer-assisted Statistical Product and Service sollution (SPSS) for windows version 16. Results of this research is to test the normality of family support variables have p = 0.192 (p> 0.05) so that the variable has a family support normal distribution and motivational variables entered SMK has p = 0.217 (p> 0.05) so that the variables entered vocational motivation has normal distribution so that it can be concluded that each variable has a normal distribution of data distribution. Test linieritasnya enter vocational motivation and family support showed linearity F = 0.035 with a significance level (p) 0.851 (p> 0.05), with the value of F deviation from linearity at 1.126 level of significance (p) 0.35 (p>0.05 ) so it can be concluded that the motivations log linear SMK with family support. As for the test this hypothesis showed no association between family support and motivation go SMK, with a correlation coefficient r = 0.021 with a significance level of p = 0.854 (p> 0.05). It is concluded in this study the hypothesis is rejected by the family support category at 91.25% and 100% motivation to enter vocational school.Keywords: Continuing vocational Motivation, Family Support.